Feminine Hygiene and Vaginal Douche Practices in Middle-aged Women - Sukhee Ahn (Korean Society of Women Health Nursing, 2013)
PURPOSE: The study was done to survey feminine hygiene and vaginal douche practices in middle-aged women to obtain basic information for public health education. METHODS: With a descriptive survey design, 134 middle-aged women who have menstrual period were recruited via convenience sampling. Survey contents were from the study by Czerwinski (2000) regarding feminine hygiene and vaginal douching practices. After obtaining IRB approval, a self-administered structured questionnaire was distributed to study participants. RESULTS: Mean age of middle-aged women was 46.88 years old. Fifty-six percent of the women practiced vaginal douching. Women performed douching with water (68%), commercial products (13%), soap (12%), and vinegar-mixed water (6%) for clean and fresh feeling, removal of unpleasant odor, and removal of vaginal discharge. Vaginal douche practice was significantly related to a history of vaginitis. CONCLUSION: The study results indicate that most of the women practiced inadequate feminine hygiene especially in douching, suggesting that is important to develop education programs on feminine hygiene practices for women of all ages, especially regarding douching and hand washing before and after changing pads or tampons.